PERANAN GURU FIKIH DALAM PENINGKATAN KARAKTER RELIGIUS DI MAN 3 PADANG PANJANG - M. Yemmardotillah (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2022)
The purpose of this dissertation is to describe the fikih guru peran in terms of enhancing siswa religious character. In addition to teaching the fundamentals of fikih, guru fikih also has a special responsibility to provide accurate suri tauladan for the development of strong siswa characters. The current study makes use of a quantitative deskriptif methodology. Data collection techniques include observation, documentation, and documentation with data analysis through redaction, presentation of data and drawing conclusions, and verification. The findings demonstrated the importance of fikih professors in developing the religious character of MAN 3 Padang Panjang students, particularly the teacher's role as a motivation for their academic pursuits. With the intention of helping students grow more in their Islamic culture, give them more praise than punishment, encourage optimism in fikih courses, and celebrate accomplishments. Additionally, the fikih teacher's role as a mentor in fostering the religious character of MAN 3 Padang Panjang students requires that the teacher try to offer a variety of information about religious culture that is required for the fikih teaching and learning process, as well as evaluate the fikih learning outcomes at each stage. He engages in religious and cultural activities.